Analysis of Soybean Raw Material Inventory Capacity on Tempeh Production Volume in Sanan Village, Malang City - Trisna Enjelia Lider; Gunawan, Cakti Indra; Fendiyatmi Kusufa (International Journal of Management and Business, 2025)
Sanan Village in Malang City is known as the center of the tempeh industry, with production reaching 1.8 tons per day. The importance of analyzing the capacity of soybean raw material supplies and its impact on the volume of tempeh production in Sanan Village. This research aims to analyze the current soybean raw material inventory capacity available in Sanan Village, assess the effect of soybean raw material inventory capacity on tempeh production volume at Mrs. Anjarwati's MSME, Sanan Village, recommend strategies to increase soybean raw material inventory capacity in supporting more optimal tempeh production. This research method uses MRP analysis with a research duration of 2 months from December 2024 to January 2025. The results of the study show that the raw material inventory capacity is sufficient, with appropriate stock to support the smooth production of tempeh. Remaining stock if the business manager utilizes raw materials optimally. Based on the MRP analysis, the soybean raw material inventory and supporting the volume of tempeh production by focusing on improving the quality and quality of the tempeh produced. For further researchers, it is hoped that further researchers will study more aspects of the maintenance of the production process, both from machines or tools to produce products and maintenance of the quality of the available raw materials.